Answers

2015-09-16T19:56:58+05:30
That is the formula of x2+y2= (x+y)(x+y) 
0
i don`t know very well refer to diganta`s ANS.
(x+y)(x+y)=x^2+xy+xy+y^2=x^2+2xy+y^2=(x+y)^2.So,how can it be (x^2+y^2) ?
thats what i am saying to sahil verma
i have x2 - y2 = (x - y)(x + y) in mind so i ans..
^2 + y^2 = x^2 + 2xy +y^2 - 2xy
= (x + y)^2 - 2xy is right ans.
2015-09-16T20:24:55+05:30
X^2 + y^2 = x^2 + 2xy +y^2 - 2xy
              = (x + y)^2 - 2xy
x^2 + y^2 = x^2 - 2xy + y^2 + 2xy
              = (x - y)^2 + 2xy

∴ (i) x^2 + y^2 = (x + y)^2 - 2xy.
   (ii) x^2 + y^2 = (x - y)^2 + 2xy.
0